The effectiveness of the leadership transformation programme among off-campus student at University Malaysia Pahang - Rohana, Hamzah; Nurul Ain Fatehah, Baharuddin; Wan Jumani, Fauzi; Muhammad Afzamiman, Aripin; Hafizah, Harun (2018)
The social issues involving many university students are quite serious as has been reported in the mainstream and social media. All parties need to work together to help these students before the issues worsen. Additional focus should be given to off-campus students as they are more susceptible to negative influences such as friends and the surrounding environment. In order to identify the causes of these problems, a preliminary study was carried out. Results from the preliminary study showed that there were four major problems which are, (1) relationship with the Creator, (2) self-management (3) social relationship with housemates, as well as (4) housekeeping management and upkeep. Therefore, to help the students overcome these problems, an intervention programme named Transformation Leadership Programme for Off-Campus Students was designed. Despite using a mixed method design approach to investigate the effectiveness of the intervention programme, the findings reported in this study are based only on the quantitative data (in the form of pre-and post-test results) collected from the 40 respondents of this study. Furthermore, the researcher also evaluate the impact of the programme on students’ academic achievement. The result shows that, there is no significant difference for the variable, ‘Respondents’ belief in the Creator’ although the mean value increased in the post-test. Apart from that, the findings also show significant improvements in the other three variables assessed, namely the transformation of self-leadership, the transformation of social leadership (housemates) and the transformation of environment leadership (housekeeping management and upkeep). There was also positive impact on off-campus students’ academic achievement when the number of respondents with CGPA below 2.5 decreased. Therefore, the findings show that the programme is successful in helping off-campus students to understand and make a connection between the value of belief in the Creator (spiritual intelligence) with the exercise of social responsibility as a leader to oneself, others and the environment (their rented property). Consequently, it is hoped that this programme could be implemented more widely to benefit more off-campus students as this would contribute to develop a more holistic and comprehensive university student management system in the future that is able to factor in off-campus students social issues.